2017
DOI: 10.1007/s10461-017-1760-3
|View full text |Cite
|
Sign up to set email alerts
|

Self-Report and Dry Blood Spot Measurement of Antiretroviral Medications as Markers of Adherence in Pregnant Women in Rural South Africa

Abstract: Antiretroviral (ARV) adherence is essential to prevent mother-to-child transmission of HIV. This study compared self-reported adherence versus ARV detection in dried blood spots (DBS) among N=392 HIV-infected pregnant women in South Africa (SA). Women completed two self-reported adherence measures [Visual Analog Scale (VAS), AIDS Clinical Trials Group Adherence (ACTG)]. Adherence was 89% (VAS), 80% (ACTG), and 74% (DBS). Self-report measures marginally agreed with DBS (VAS: Kappa=0.101, Area Under the ROC Curv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 11 publications
2
40
1
Order By: Relevance
“…In this study, DBS were used to quantify concentrations of EFV, with an overall good correlation (R 2 =0.904, p<0.001), albeit underestimation (53% ±9.5% lower) of plasma drug levels[47]. In another study, drug concentrations of parent tenofovir (TFV) from tenofovir disoproxil fumarate (TDF), lamivudine (3TC) and EFV were evaluated in a pregnant women cohort in rural South Africa, demonstrating an overestimation of adherence in self-report vs. DBS levels, but feasibility of DBS collection in this population[48]. The main limitation of these studies was the focus on parent drug concentrations in DBS, which are expected to also have short half-lives similar to their plasma counterparts, thus restricting their adherence evaluation to a qualitative yes/no information over a short period of time.…”
Section: New Pharmacologic Measures That Quantify Cumulative Drug Expmentioning
confidence: 99%
“…In this study, DBS were used to quantify concentrations of EFV, with an overall good correlation (R 2 =0.904, p<0.001), albeit underestimation (53% ±9.5% lower) of plasma drug levels[47]. In another study, drug concentrations of parent tenofovir (TFV) from tenofovir disoproxil fumarate (TDF), lamivudine (3TC) and EFV were evaluated in a pregnant women cohort in rural South Africa, demonstrating an overestimation of adherence in self-report vs. DBS levels, but feasibility of DBS collection in this population[48]. The main limitation of these studies was the focus on parent drug concentrations in DBS, which are expected to also have short half-lives similar to their plasma counterparts, thus restricting their adherence evaluation to a qualitative yes/no information over a short period of time.…”
Section: New Pharmacologic Measures That Quantify Cumulative Drug Expmentioning
confidence: 99%
“…Based on two previous studies, adherence was defined as detectable antiretroviral in dried blood spots [24], and the range of hair tenofovir concentration was 21 to 53 pg/mg when the subject took TDF 7 days/week (100% adherence) [36], we defined hair measure of optimal adherence as hair tenofovir concentration above LOQ, and suboptimal adherence as hair tenofovir concentration below LOQ.…”
Section: Hair Collection and Assaymentioning
confidence: 99%
“…Several studies have examined the concurrent validity of various self-reported measures with other devicebased measures [17] or biological measures (e.g., viral load, and antiretroviral concentration in various pharmacokinetic metrics) [10,19,[24][25][26]. While these studies provide important information regarding the validity of self-reported measures, data are limited in Chinese PLHIV and comparison of those self-reported measures with long-term biological measures of adherence.…”
Section: Introductionmentioning
confidence: 99%
“…7 Unlike other measures of adherence, the Medication Adherence Rating Scale (MARS) describes an individual's medication adherence in three dimensions: medication adherence behavior, attitude toward taking medication, and negative side effects and attitudes to psychotropic medication. 7 Indeed, self-report measures of medication-taking behavior overestimate adherence when compared to objective measures, 8 and this is perhaps why it has been argued that aside from medication-taking behavior, self-report measures should also assess for barriers to adherence and beliefs. 9 The MARS has not been well utilized in sub-Saharan Africa: the authors only identified one previous report.…”
Section: Introductionmentioning
confidence: 99%